2016
DOI: 10.1111/jcmm.12939
|View full text |Cite
|
Sign up to set email alerts
|

CD151 mediates netrin‐1‐induced angiogenesis through the Src‐FAK‐Paxillin pathway

Abstract: Crosstalk between the nervous and vascular systems is important during development and in response to injury, and the laminin‐like axonal guidance protein netrin‐1 has been studied for its involvement in angiogenesis and vascular remodelling. In this study, we examined the role of netrin‐1 in angiogenesis and explored the underlying mechanisms. The effect of netrin‐1 on brain tissues and endothelial cells was examined by immunohistochemistry and western blotting in a middle cerebral artery occlusion model and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Previous studies have reported that FAK may be one of the primary downstream effectors of NTN1, functioning through the receptors DCC and neogenin (15,16). Furthermore, it has been reported that NTN1-induced cell proliferation and migration is mediated by the activation of FAK (17,25). The results of the present study suggest that FAK phosphorylation was decreased following NTN1 knockdown in GC cells, whereas NTN1 overexpression had the opposite effect.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies have reported that FAK may be one of the primary downstream effectors of NTN1, functioning through the receptors DCC and neogenin (15,16). Furthermore, it has been reported that NTN1-induced cell proliferation and migration is mediated by the activation of FAK (17,25). The results of the present study suggest that FAK phosphorylation was decreased following NTN1 knockdown in GC cells, whereas NTN1 overexpression had the opposite effect.…”
Section: Discussionsupporting
confidence: 55%
“…NT-1 also inhibited the notch signaling pathway after ischemic stroke [ 34 ]. In the process of angiogenesis and vascular remodeling, an NT-1/focal adhesion kinase (FAK)/Src signaling axis was also reported to be an important pathway [ 35 ]. In addition, NT-1 phosphorylated AMP-activated protein kinase (AMPK) and reduced the phosphorylation of mammalian target of rapamycin (mTOR) and P70S6K in a spinal cord injury model [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular effectors are crucial in regulating the effect of NT-1. When introduced to proliferating endothelial cells, NT-1 was reported to increase the expression of inducible nitric oxide synthase (iNOS) and cluster of differentiation (CD) 151 [ 31 , 35 ]. NT-1 was also shown to be a regulator of nuclear factor kappa B (NF-κB) when inhibiting prostaglandin E2 (PGE-2) production [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other proteins such as syndecan-1 as well as tetraspanin CD151 that are known to regulate, relate to, or interact with ITGB4, are also implicated in diverse processes such as the examples used here of viral infection and cancer [69], and also signal through Src [70]. This cohort of proteins has likewise been isolated together with the integrin in secreted microvesicles and exosomes [7173], where 12-HETE can also be found [54], thereby implicating this axis in tissue programming.…”
Section: Discussionmentioning
confidence: 99%